IMPLIKASI PENGGUNAAN MERK KOPI TIAM BERDASARKAN HUKUM MEREK DI INDONESIA - Elza Syarief; Rina Shahriyani Shahrullah; Febri Jaya; Edward Banner Purba (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
The brand of the Kopitiam has been used for a long time. However, this circumstance has changed after an ownership claim of the Kopitiam brand on February 8, 2012. It was claimed that the trademark holder declared himself as the exclusive right holder for the “Kopitiam” brand based on the registration number: 371718, dated November 13, 1996 for services of food and beverage, cafeteria, coffee shop and similar items. Therefore, this paper aims to conduct a deeper discussion of the implications of the claim according to the Indonesian law. As the result of the discussion, based on the various facts it was found that there was a potential violation of the registration of the Kopitiam trademark, however as the consequence of this registration there must be a legal action taken to the court in the form of a lawsuit from the aggrieved party who was suffered loss due to the said registration. Keywords : Kopi Tiam, Brand, Trademark Dispute